Characterizing the source contributions and spatial controls of heavy metals in stream sediments in northwestern China’s mining areas - Xue, Sheng; Qi, Changwei; Zhong, Yongsheng; Ji, Bingyan; An, Zhao; Ma, Shenglin; Li, Zhenghui; Li, Shengfu; Wang, Guoxia (Frontiers in Environmental Science, 2026)
Heavy metal pollution in stream sediments of the Qaidam Basin, northwestern China, has attracted widespread attention due to its environmental and ecological implications. Estimate of the sources of heavy metals in sediments and their driving factors is a pre-requisite for the management and control of heavy metal pollution. In this study, a large number of stream sediment samples (n = 8,280) from typical alluvial fans in the Qaidam Basin were collected for heavy metal analysis. Positive matrix factorization (PMF) was employed to explore their sources and spatial contributions. The findings indicate that mineralization (39.1%) and soil parent material (34.3%) are the predominant sources of heavy metals in sediments, accounting for over 70% of the total. The contributions of industrial activities (19.1%) and atmospheric deposition (7.4%) are significant and cannot be disregarded. Furthermore, the presence of heavy metals in stream sediments demonstrates significant spatial variability (p < 0.05). The spatial distribution of natural sources is subject to the influence of geological conditions, exhibiting congruence with the spatial distribution of strata and structures. This study provides a foundation for implementing site-specific heavy metal risk mitigation strategies in mining areas.